Estudo do biomimetismo da asa da tesourinha aplicado ao perfil aerodinâmico NACA 4412 - Ferreira, Felipe Raniere Reis (2024)
Human curiosity has always led to technological developments, one of them being the ability to fly using the aerodynamic concepts of birds. At the beginning of the 20th century, the Wright brothers achieved the first powered airplane flight, and sometime later Santos Dumont repeated this feat with the 14-Bis. This led to the development of new aircraft with various wing profiles and geometries, which were widely applied in the First World War. Subsequently, there were new developments in the field of aerodynamics, especially in the area of wings, inspired by nature, such as birds. Using this concept, called biomimetics, this study looked at the behavior of the wing of the Tyranussavana bird, popularly known as the Fork-tailed Flycather. In this analysis, it was found that its rêmige (the bird's largest feathers) has a different shape to the feathers of other birds. This feature prompted the development of a biomimetic of this wing feather, with an application for cargo planes, due to its ability to travel long distances efficiently, like the scissorbill. To check the behavior of this feather, a wing was developed with biomimicry (imitating the Fork-tailed flycather feather) and another without biomimicry, using a NACA 4412 profile. Using these wings, a comparative analysis was carried out to gain a better understanding of the aerodynamic phenomena of lift, drag, pressure and speed. Both wings were modeled in the student version of Solidworks and simulated in Ansys Fluent version 19.2. The analyses in this study involved angles of attack from 0° to 15° for both wings, with the biomimetic wing showing aerodynamic advantages from 5° to 15°. This result shows the effectiveness of biomimicry applied to aviation.